Analysis of Exhibition Service Quality Dimensions: A Case in Indonesia - Simangunsong, Eliot; MG. Agesti Setyorini (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Exhibition management is a complex process which is why it is important to understand the elements of the exhibition that attract potential visitors and exhibitors to create a successful exhibition where there are many visitors and exhibitors. There are many factors, e.g., venue facilities, contractors, ease of access, and recreation around the location that plays an important role that form the basis of a successful exhibition. However, there is no consensus among researchers on this issue. Previous research has different arguments as to which factors are more important, although most agree that overall satisfaction with the quality of exhibition services relates to visitor satisfaction. Visitor satisfaction is hypothetically closely related to the dimensions of SERVQUAL and therefore, this study aims to identify components of service quality extracted from previous research that have a significant influence on the quality of exhibitions and therefore increase the source of revenue for exhibition companies. The unit of analysis in this research are organizer companies and their customers. SPSS software used to analyze data and analyze confirmatory factor analysis using SMART-PLS produces a modified SERVQUAL model which shows that non-tangible has the strongest influence on service quality, followed by cluster effect, other and tangible dimensions. Keywords: service quality, exhibition, servqual, purchase intention, management